2018
DOI: 10.1042/cs20170262
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 play opposite role in autophagy associated with cisplatin-induced acute kidney injury

Abstract: Acute kidney injury (AKI) is considered an inflammatory disease in which toll-like receptors (TLRs) signaling pathways play an important role. The activation of TLRs results in production of several inflammatory cytokines leading to further renal damage. In contrast, TLRs are key players on autophagy induction, which is associated with a protective function on cisplatin-induced AKI. Hence, the present study aimed to evaluate the specific participation of TLR2 and TLR4 molecules on the development of cisplatin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 50 publications
0
62
0
Order By: Relevance
“…TLR signaling pathways play an important role in AKI, and TLR2 but not TLR4 plays a protective role in cisplatin‐induced AKI . The protective role of TLR2 is associated with autophagy and HO‐1.…”
Section: Discussionmentioning
confidence: 99%
“…TLR signaling pathways play an important role in AKI, and TLR2 but not TLR4 plays a protective role in cisplatin‐induced AKI . The protective role of TLR2 is associated with autophagy and HO‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs), membrane passing proteins, are abundantly expressed in immune cells and renal tissue, and considered as autophagy mediators. For instance, it was reported that TLR2 induced autophagy in acute kidney injury model made by cisplatin and improved the global renal tissue parameters [124]. Wen et al found that TLR2 and TLR4 were up-regulated in hippocampus neurons of epilepsy mice.…”
Section: Cross-regulation By Toll-like Receptor-ligand Signal Pathwaymentioning
confidence: 99%
“…The interaction of Toll-like receptors (TLR2 and TLR4), cisplatin-induced AKI, and HO-1 has been recently studied [86]. In response to cisplatin, TLR2 deficiency worsens renal injury, while these effects were not observed in TLR4-deficient mice.…”
Section: Ho-1 and Autophagymentioning
confidence: 99%